Development of cold plates for enhanced single-phase cooling applications - Chong, James Khi Tse (Nanyang Technological University, 2020)
This project investigates the heat transfer performance enhancement of 3D-printed oblique fins in a louvred arrangement in a liquid cold plate. It investigates the performance of such fin arrays in single-phase forced convection in the fluid medium of water. The designs tested were drawn using SOLIDWORKS, a Computer-Aided-Design software, and were subsequently fabricated using an additive manufacturing method, Selective Laser Melting. Three specimens were printed, each with a different angle of rotation of the oblique fins (0°, 15°, and 30°). Experimental and numerical investigations were conducted to ascertain the heat transfer capabilities of each design and specimen. Experiments varied the mass flow rate between 10 g/s and 20 g/s at two different heat inputs of 400 W and 500 W. The results obtained were then compared to results from a numerical simulation study using ANSYS Fluent for validation. The results demonstrate that rotated oblique fins in a louvred arrangement enhances the heat transfer performance of a liquid cold plate, and that the larger the angle of rotation, the greater the thermal capability. The louvred arrangement also impeded axial flow and increases the pressure drop penalty across the specimen, with the increase being non-linear to the angle of rotation. Evaluating each of the designs using a performance index, it is observed that the fin array with no rotation produces the greatest heat transfer performance per unit of pressure drop penalty, at an average of 47.1% higher than the array featuring oblique fins rotated at 15º, peaking at 52.5% higher at the highest mass flow rate, even though the other two designs produced lower base surface temperatures and larger heat transfer coefficients.